Hermeneutika HERMENEUTIKA FAZLUR RAHMAN: DOUBLE MOVEMENT DALAM PENAFSIRAN AL-QUR’AN - Nur Anis Rochmawati; Muwafiq, Ahmad (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2024)
Fazlur Rahman builds the assumption that the Qur'an must be able to be understood holistically. An idea that is at a later stage expressed in the method of double movement hermeneutics. The idea of ​​contextualizing the values ​​of the Qur'an is the starting point in this study. The resulting conclusion, departing from his understanding of hermeneutics, Fazlur Rahman succeeded in concocting a way to understand the Qur'an through what is called a double motion; from the present situation to the time the Qur'an was revealed, and then, from the time of the Qur'an back to the present situation. The main mission of the double movement is to find the moral ideal of the Qur'an rather than its specific legal. Rahman's contribution in changing the face of Islamic law can be seen in the application pattern of 'non-Muslim leadership'. Keyword: Fazlur Rahman, Double Movement, Hermeneutics